Computer-based psychological treatments for depression: A systematic review and meta-analysis - Richards, Derek; Richardson, Thomas (Clinical psychology review, 2012)
The aim of the paper was to systematically review the literature on computer-based psychological treatments for depression and conduct a meta-analysis of the RCT studies, including examining variables which may effect outcomes. Database and hand searches were made using specific search terms and inclusion criteria. The review included a total of 40 studies (45 published papers), and 19 RCTs (23 published papers) were included in a standard meta-analysis. The review describes the different computer-based treatments for depression, their design, communication types employed: synchronous, asynchronous, and face-to-face (F:F); alongside various types and frequency of support delivered. The evidence supports their effectiveness and highlights participant satisfaction. However, pertinent limitations are noted. Across 19 studies the meta-analysis revealed a moderate post-treatment pooled effect size d=.56 (95% confidence interval [CI] −.71, −.41), Z=7.48, p<.001). Supported interventions yielded better outcomes, along with greater retention. The results reported statistically significant clinical improvement and recovery post-treatment. The review and meta-analysis support the efficacy and effectiveness of computer-based psychological treatments for depression, in diverse settings and with different populations. Further research is needed, in particular to investigate the influence of therapist factors in supported treatments, the reasons for dropout, and the maintenance of gains post-treatment. ► Computer-based psychological interventions for depression are effective. ► A range of different interventions, communication types and support types exist. ► Improvements in depression are significant post-treatment with many recovering. ► Improvements are maintained at follow-up, but less pronounced. ► Supported interventions yield better outcomes and greater retention.